European external quality assessments for identification, molecular typing and characterization of Staphylococcus aureus. (7th August 2018) - Deplano, Ariane; Dodémont, Magali; Denis, Olivier; Westh, Henrik; Gumpert, Heidi; Larsen, Anders Rhod; Larsen, Jesper; Kearns, Angela; Pichon, Bruno; Layer, Franziska; Schulte, Berit; Wolz, Christiane; et al.
Abstract: Objectives: We present the results of two European external quality assessments (EQAs) conducted in 2014 and 2016 under the auspices of the Study Group on Staphylococci and Staphylococcal Infections of ESCMID. The objective was to assess the performance of participating centres in characterizing Staphylococcus aureus using their standard in-house phenotypic and genotypic protocols. Methods: A total of 11 well-characterized blindly coded S. aureus ( n  =   9), Staphylococcus argenteus ( n  =   1) and Staphylococcus capitis ( n  =   1) strains were distributed to participants for analysis. Species identification, MIC determination, antimicrobial susceptibility testing, antimicrobial resistance and toxin gene detection and molecular typing including spa typing, SCC mec typing and MLST were performed. Results: Thirteen laboratories from 12 European countries participated in one EQA or both EQAs. Despite considerable diversity in the methods employed, good concordance (90%–100%) with expected results was obtained. Discrepancies were observed for: (i) identification of the S. argenteus strain; (ii) phenotypic detection of low-level resistance to oxacillin in the mecC -positive strain; (iii) phenotypic detection of the inducible MLSB strain; and (iv) WGS-based detection of some resistance and toxin genes. Conclusions: Overall, good concordance (90%–100%) with expected results was observed. In some instances, the accurate detection of resistance and toxin genes from WGS data proved problematic, highlighting the need for validated and internationally agreed-on bioinformatics pipelines before such techniques are implemented routinely by microbiology laboratories. We strongly recommend all national reference laboratories and laboratories acting as referral centres to participate in such EQA initiatives.